Environmentally friendly covalent coupling of proteins onto oxidized cellulosic materials. (29th August 2019) - Haske-Cornelius, Oskar; Weinberger, Simone; Quartinello, Felice; Tallian, Claudia; Brunner, Florian; Pellis, Alessandro; Guebitz, Georg M.
Abstract : Cellulose is a biodegradable and renewable material that is one of the most abundant biopolymers with many different applications from low value newsprint products to high value biomedical sensor devices. Abstract : Cellulose is a biodegradable and renewable material that is one of the most abundant biopolymers with many different applications from low value newsprint products to high value biomedical sensor devices. In the last years, the demand of functionalized cellulose for the development of new packaging materials was constantly rising. In this study, a new two-step method for surface functionalization of cellulose sheets and fibers involving oxidation by 2, 2, 6, 6-tetramethylpiperidinyloxyl (TEMPO) followed by coupling of different proteins was investigated. The cellulose oxidation was monitored via FT-IR at 1610 cm −1, photometrically via toluidine blue staining and via titration for the determination of the –COOH group concentration. TEMPO oxidation increased the amount of –COOH groups from around 0.2 to more than 1.4 mmol g −1 when NaClO2 /NaClO regeneration was used. The TEMPO/laccase system instead led to 0.7 mmol g −1 of –COOH groups (determined via HCl titration). The oxidation was monitored over time and showed that 50% of the reaction were completed within the first 60 min of reaction time. Coupling of protein-based hydrophobins or bovine serum albumin using the EDAC/NHS system led to the desired increase in hydrophobicity and detection of protein on cellulose. Coupling was investigated using contact angle measurements and SEM microscopy paired with elemental analysis for oxygen and nitrogen. Hence, the coupled hydrophobins led to a significant increase of the initial contact angle by 33% with water drop stability of over 200 s. In contrary, pure cellulose obtained no visible water drop and for surfaces with uncoupled hydrophobins no stable contact angle, with a soaking time dropping to 55 s was achieved. As a result, the thorough study revealed that the new combinatorial approach of surface functionalization and protein coupling led to the successful increase of hydrophobicity.